Information needs factors affecting pain experience among patients with cervical cancer stages III and IV at the Kenyatta National Hospital: A descriptive phenomenology study (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Cervical cancer is the leading cause of cancer-related deaths among women in Kenya.Patients present late when the cure is unattainable and have an impaired quality of life (QoL). Pain is theworst and most common cause of impaired QoL. Poor control is due to a focus on the physical aspect ofpain only rather than the holistic approach that also considers the nonphysical factors, includingpsychological, social, spiritual, economic, and information needs aspects of pain. Information need isdefined as a state in which one perceives a gap between information and knowledge available to solve aproblem. There is inadequate information exchange between health care providers and cervical cancerpatients in Kenya, with such patients reporting that inadequate information prolonged their suffering asthey sought diagnosis and treatment. There have been recommendations that communication guidelinesbe developed, and communication training skills be developed in a culturally relevant way. Differences incultural and socioeconomic contexts may impede this goal.Objective: To explore information needs factors among patients with cervical cancer stages III and IV atthe Kenyatta National Hospital.Methods: Qualitative research using a descriptive phenomenological study involving fifteen in-depthinterviews and five focus group discussions was conducted.Results: This study revealed poor methods of breaking bad news, conflicts in the disclosure of bad newsto patients, inadequate information on the investigations and procedures needed, and doctors’unavailability to provide detailed information, especially those that require seeking money from relatives.Conclusion: Information needs remain a gap affecting pain experienced by cervical cancer patients.